Gaziantep Ekonomisinin Ortadoğu Açısından Önemi - (:unkn) unknown (My University, 2016)
Gaziantep tarih boyunca birçok medeniyete ev sahipliği yapmış, Türkiye'nin en önemli sanayi ve ticaret merkezlerinden biridir. Sahip olduğu ticaret potansiyeli ve girişimcilik ruhuyla dünya piyasalarına entegre olmuştur. Türkiye'nin güney sınır komşularıyla yakın ticari ve ekonomik ilişkiler geliştirerek bölgede sanayi ve ticaret merkezi olmayı başarmıştır. Komşu ülkelerle sınır ticaretini geliştirerek, kendine ve Türkiye ekonomisine önemli katkılar sağlamıştır. Bölgenin en gelişmiş ili olan Gaziantep, Türkiye'nin Ortadoğu'ya açılan en önemli ticaret kapısıdır. Ortadoğu ülkeleriyle geliştirdiği ikili ilişkiler ekonomik kalkınmayı daha da hızlandırmıştır. Ayrıca Ortadoğu ülkeleri ile Batı ve Asya bloğu arasında mal transferlerinde aracı konumdadır. Ortadoğu bölgesinin sürekli hareketli olması ve bölgede eksik olmayan savaş, ekonomik düzeni bozmakta ve yaşanan olumsuzluklar ihracat ve ithalatı olumsuz etkilemektedir. Gaziantep ekonomisi giderek gelişmekte ve Ortadoğu ihracatına kısmi azalmalarla birlikte katkısı devam etmektedir

During centuries Gaziantep has hosted many civilizations being one of the most important industrial and trade center in Turkey. Endowed with its trade potential and entrepreneurial spirit it easily integrated in the international markets. Strengthening its trade and economic ties with neighboring countries it evolved in important regional industrial and trade hub. By developing trade ties with the neighboring countries Gaziantep also provides important spillovers to the other municipalities and regions of Turkey. As the most developed city in the region Gaziantep is crucial gate to the markets of the Middle East. Enhancing economic relationships with the Middle Eastern countries it had important implications on speeding the economic development. It is also a mediator in commodity transfer between Western and Eastern countries. Continuous movements and war conflicts in the region had destructive effects on economic environment. During the periods of intense war conflicts the economy of Gaziantep is being seriously disbalanced and hit by recession cycles. However, inspite of these negativities Gaziantep is continuing with decreasing its export share to the Middle East countries.In this paper a general literature regarding the city of Gaziantep is being consulted along with the help of table and graphical tools in the analysis of the advantages and disadvantages, also in the same time economic importance of the Gaziantep for Turkey and Middle East region as well is being stressed and some suggestions are being explored in th concluding part
The Importance Of Gaziantep City Economy For The Middle East
Keywords: İktisat; Coğrafya; Uluslararası İlişkiler; Siyasi Bilimler